Trade liberalisation and product mix adjustments: Evidence from South African firms - Fall, Falilou (OECD Publishing, 2020)
Theoretical and empirical studies on multi-product firms have shown that firms adjust their product mix in response to trade liberalisation. This paper uses the South African Revenue Service (SARS) and National Treasury (NT) firm-level panel to assess the response of South African firms to trade policy changes and demand shocks in destination markets between 2010 and 2016. This paper shows that South African multi-product manufacturers shift their exports towards their core products when competition intensifies in their export destinations and that these dynamics lead to productivity gains at the firm level. Also, trade liberalisation policies in the destination country positively affect the number of exported goods (extensive margin) as well as the average value of already exported products (intensive margin) for multi-product exporters, whereas restrictive measures negatively affect the extensive margin. Regarding trade policy measures, results suggest that tariff liberalisation only amplifies the adjustment of South African exporters if tariff cuts affect South African firms directly, while tariff cuts benefitting other foreign competitors mitigate within firm adjustments. By contrast, the reduction of Non-Tariff Measures (NTMs) always positively affects South African exporters
Keywords: Economics; South Africa